Diversifica????o na gest??o estrat??gica em microempresas de ensino do surfe: um estudo multicasos - Cruz, Ana Carolina Costa (2015)
We can observe that there are several strategies that guide the competitive, one of them is diversification. This paper presents a study of diversification in the strategic management of surfing teaching of micro enterprises (MEES) of Rio de Janeiro. In the case of MEES, there are characteristics that make it very important to diversify their survival and development. Therefore, we chose to study the subject in this type of company. The research analyzed the diversification process used by MEES of Barra da Tijuca and of Recreio dos Bandeirantes, in the city of Rio de Janeiro, in order to demonstrate the impacts resulting from the choice of such a strategy. Considering the diversification of products (goods and services), we discuss the strengths and limitations of the strategies that promoted diversification in the companies studied. The research was a multi-case study, exploratory and qualitative. In data processing, mainly collected through semi structured interviews, they were analyzed with the support of the analysis of Atlas-ti qualitative data software. Develop intra and intercasos analysis, thus explaining the diversification process in seven firms. Comparing the cases studied, we identified best practices in strategic diversification of business management. All MEES diversified horizontally, ie expanded their services to additional markets - for example, surf trips (trips to surfing) and stand up paddle lessons. We found that vertical diversification of some occurred with the manufacture or repair of surfboards. There were also independent diversification (diversification with little or no relation to the services already existed before): petitions, bike rentals, pilates and yoga classes, massage and hosting customers. In most cases investigated, the diversified leaders to meet a customer demand. Another opportunity arose to diversify the experiences, learning and internal knowledge available in the company, which shows that the allied training to previous experience is related to the diversification in their business option. It is noticed that there is a sporadic concern for strategic management in MEES and long periods of attention exclusively focused on operational and administrative problems. On the other hand, the MEES owner-managers demonstrate awareness of the need to innovate and generate a differentiation by creating new services. Although not always performed as intended, a common goal to managers of MEES is to achieve a given amount of sales level (or servicing), but with high quality, paying attention to the shortage of human resources who have education and training to work this type of company. Finally, diversification in MEES brought higher revenues for companies, promoted the loyalty of customers who engage in one or more of the company's services, and has become a differentiating from competitors, reducing competition by price. As a result of a diversification strategy, the MEES are surviving in the long term and stabilized the financial company.